Analisis Pengalaman Pengguna pada Website E-Commerce (Studi pada klikindomaret.com dan alfacart.com) - Wilda Kusnawati; Retno Indah Rokhmawati; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The use of e-commerce in Indonesia became one of the proof of business development in Indonesia that began to move online. The number of use in e-commerce makes two companies engaged in the field of minimarkets indomaret and alfamart start to create their website. This study aims to compare two e-commerce that has characteristics and business processes are the same in how them facilitating users from the usability side also from user experience side with using media website klikindomaret and alfacart. There are 2 method of analisys to analyze the data that was subjectively by distributing Questionnaire from User Experience Questionnaire (UEQ) which has 6 aspects: attractiveness, efficiency, perspicuity, dependability, stimulation and novelty to 20 respondents and objectively by testing the respondent directly in website usage using scenario with parameter task success rate, time per completed task, number of clicks during task competence and error during task performance to 6 respondents. Respondents are students from 18-24 years old who have never operated these two websites. The results of the analysis showed that in the subjective research the respondents gave positive tendency impression with the average value reaching the positive level (good). For objective research shows a high success rate of respondents even though they are the first time to operate the website.